Creation of the Short Documentary 'Sampah Siapa? Siapa Sampah?" for Waste Management Awareness and Sustainable Development in Surabaya - Budiono, Theodore Michael; Widodo, Fatahayan; Sumerta, I Made Restu Kinandana; Candra, Vinsen; Dinata, Laurensius Rubben Surya (VCD: Journal of Visual Communication Design, 2023)
The Sustainable Development Goals (SDGs) represent a global action plan endorsed by world leaders, including Indonesia, comprising 17 Goals and 169 Targets, the SDGs aspire to be achieved by 2030. This study focuses on environmental preservation, aligning with Goal 15 (preserving terrestrial ecosystems), Goal 6 (access to clean water and sanitation) and Goal 14 (conserving marine ecosystems). Environmental degradation remains a detrimental factor in disrupting Earth's natural ecosystems, impacting various aspects of the environment and giving rise to problems such as floods, which inevitably lead to various diseases, bacteria, and even viruses. Waste is generated, ranging from household refuse to industrial waste. Our current challenge lies in a lack of public awareness regarding the importance of responsible waste sorting. We hope that the public will shift their perspective on waste from being a "negative" aspect to a resource that can be repurposed for the betterment of society and the environment. To raise awareness, we have created short videos featuring testimonies from individuals affected by waste pollution in their communities. Waste management serves as a solution and is a crucial element of our video content, as it not only raises awareness but also imparts essential knowledge to the public, helping to reduce waste generation and simplify the waste separation process. This, in turn, minimizes the residual impact of waste disposal. Our study underscores the significance of promoting waste management awareness to achieve the SDGs. Through educational videos and public engagement, we aim to inspire individuals to take proactive steps in preserving our environment and building a sustainable future.